2020
DOI: 10.24320/redie.2020.22.e02.2075
|View full text |Cite
|
Sign up to set email alerts
|

Mediación parental del uso de Internet desde una perspectiva de género.

Abstract: El objetivo de esta investigación es conocer la percepción de los progenitores sobre el uso de Internet de sus hijos/as, así como sus prácticas de mediación para promover los beneficios y evitar los riesgos en la red. Se presenta un estudio descriptivo por encuesta a 186 progenitores cuyos hijos cursaban 3o. y 6o. curso de educación Primaria. La mayoría mostró tendencias de mediación “puras” de tipo instructivo, seguidas por los tipos compartido y restrictivo, pero un tercio presentó tendencias de mediación mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
1
0
1
Order By: Relevance
“…Researchers such as Martínez et al (2020) have found that in the nine to 12 age range, boys are given more liberty in using phone cameras, while in the 13 to 17 age range, both sexes have similar restrictions. Hence, parental mediation in digital devices is more restrictive for girls (Bartau-Rojas et al, 2020). Other studies have looked at changes in the context of family life with regard to time spent in conversation, relaxation and distraction mediated by screens (Madigan et al, 2019; Pew Research Center, 2018).…”
Section: More Media Booming Education Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers such as Martínez et al (2020) have found that in the nine to 12 age range, boys are given more liberty in using phone cameras, while in the 13 to 17 age range, both sexes have similar restrictions. Hence, parental mediation in digital devices is more restrictive for girls (Bartau-Rojas et al, 2020). Other studies have looked at changes in the context of family life with regard to time spent in conversation, relaxation and distraction mediated by screens (Madigan et al, 2019; Pew Research Center, 2018).…”
Section: More Media Booming Education Opportunitiesmentioning
confidence: 99%
“…Investigadores como Martínez et al (2020) han descubierto que, en el rango de edad entre nueve y 12 años, los niños tienen más libertad para utilizar la cámara del móvil, mientras que entre 13 y 17 años, se imponen restricciones similares a ambos sexos. Por tanto, la mediación parental en el uso de los dispositivos digitales es más restrictiva para las niñas (Bartau-Rojas et al, 2020). Otros estudios han analizado los cambios en el contexto familiar en relación con el tiempo dedicado a la conversación, relajación y distracción mediante el uso de pantallas (Madigan et al, 2019; Pew Research Center, 2018).…”
Section: Más Medios Múltiples Oportunidades Educativasunclassified